Do Community Treatment Orders in Psychiatry Stand Up to Principalism: Considerations Reflected through the Prism of the Convention on the Rights of Persons with Disabilities. Issue 1 (March 2019) - Newton-Howes, Giles
Compulsory psychiatric treatment is the norm in many Western countries, despite the increasingly individualistic and autonomous approach to medical interventions. Community Treatment Orders (CTOs) are the singular best example of this, requiring community patients to accept a variety of interventions, both pharmacological and social, despite their explicit wish not to do so. The epidemiological, medical/treatment and legal intricacies of CTOs have been examined in detail, however the ethical considerations are less commonly considered. Principlism, the normative ethical code based on the principles of autonomy, beneficence, non-maleficence and justice, underpins modern medical ethics. Conflict exists between patient centred commentary that reflects individual autonomy in decision making and the need for supported decision making, as described in the Convention on the Rights of Persons with Disabilities (CRPD) and the increasing use of such coercive measures, which undermines this principle. What appears to have been lost is the analysis of whether CTOs, or any coercive measure in psychiatric practice measures up against these ethical principles. We consider whether CTOs, as an exemplar of coercive psychiatric practice, measures up against the tenets of principalism in the modern context in order to further this debate.